Radiographic imaging and exposure - Fauber, Terri L. (St. Louis : Elsevier, 2021)
Master the radiography skills needed to produce high-quality images every time! With straightforward coverage of imaging principles, Radiographic Imaging and Exposure, 6th Edition describes exposure techniques and how to acquire, process, and display digital images. Not only does this book help you reduce the need for repeat images, it includes problem-solving guidelines for troubleshooting situations. Written by noted educator Terri L. Fauber, this book also provides the essential knowledge needed to pass the ARRT certification exam.
Includes bibliographical references and index.
Keywords: Radiography; Radiographic image enhancement